Comparison of the effectiveness of the personalized schroth exercise and conventional therapy for scoliosis in children with rheumatic disease - Kısa, Eylül Pınar; Tarakcı, Ela; Leblebici, Gökçe; Çaçan, Mehmet Akif; Kasapçopur, Özgür (BMJ Publishing Group, 2023)
Background: Childhood rheumatic disease is one of the most common chronic diseases in childhood and adolescence [1]. In particular, it causes weakness, pain, problems in the musculoskeletal system, displacement of the center of gravity, deteriorating biomechanics and muscle imbalance results in scoliosis [2]. Scoliosis is one of the most common musculoskeletal problems encountered in children and adolescents today. In the literature, there are many current studies describing various exercise methods (especially Personalized Schroth Exercise-PSE) that are effective on scoliosis [3, 4]. However, there are no studies investigating the effectiveness of these exercise methods in children with rheumatism. Objectives: Our study, it was aimed to compare the conventional theraphy program with PSE in children with scoliosis and rheumatic disease.
Keywords: Rheumatic Disease; Conventional Therapy; Personalized Schroth Exercise